Transmissibility-Based Operational Modal Analysis: Enhanced Stabilisation Diagrams - Gert De Sitter; Christof Devriendt; Patrick Guillaume (Shock and Vibration)
Recently it has been shown that also transmissibilities can be used to identify the modal parameters. This approach has several advantages: because of the deterministic character of the transmissibility functions, the estimated parameters are more accurate than the results obtained with the power spectra based operational modal analysis techniques. Another advantage is that the transmissibility functions do not depend on the colouring of the unknown forces. A disadvantage of the transmissibility based operational modal analysis techniques is that non-physical modes show up in the stabilisation diagrams. In this contribution it will first be shown that those non-physical modes will show up when traditional stabilisation diagrams are used. In a second step, a new approach of selecting the physical modes out of a set of estimated modes will be discussed and the new approach will be validated using data generated with an acoustical Finite Element Model. Finally, the approach will be validated using real acoustical data.